Expectation and satisfaction of managers about levels of knowledge and skills of fresh engineering graduates: the case of renewable energy - Jamal Othman Jaber (Universitas Diponegoro, 2020)
This field study aimed to examine satisfaction and expectation of managers of energy service companies and related official entities of fresh engineers’ basic knowledge and skills in fields of energy management and renewable energy technologies. The existing gaps between what is demanded in the market and engineering graduates’ skills are explored through measuring relevant required skills from managers’ point of view as well as their general satisfaction about performance and basic knowledge in related engineering fields. To achieve these goals a structured questionnaire was distributed to specialized private companies working in the installation of renewable energy systems and energy services. It was also forwarded to concerned governmental agencies and active NGOs promoting energy efficiency and environmental protection, followed by face-to-face interviews with selected experienced and specialized engineers to cross check and make sure that weaknesses and gaps in knowledge and skills required to enter the market are addressed. Statistical analysis was conducted to determine the level of satisfaction and readiness of fresh engineers to join energy companies and areas that graduates need to be improved. Results suggested that managers are not fully happy and satisfied with levels of basic engineering understanding and technical skills among newly graduated engineers from universities in Jordan. Equally important is that managers do not feel that graduates are ready to enter the market and start practical life. Main gaps identified by managers are lack of understanding of relevant engineering sciences, relatively poor technical communication skills and nearly absence of financial and managerial basics. Thus, all parties involved in engineering education, in the country, should make necessary reform in the study plans and curricula to meet the market demands.